Study of the association of folate cycle genes polymorphisms with changes in serotonin levels in patients with type 2 diabetes in the post-COVID period - Shuprovich, Angela; Komissarenko, Katerina; Zinych, Olesia; Kushnareva, Natalija (ScienceRise: Medical Science, 2025)
The aim of the work was to identify relationships between modifications of the folate cycle gene structure and serum serotonin levels, depending on the presence or absence of type 2 diabetes mellitus (DM) in patients during COVID-19 and 6-9 months after recovery. Materials and methods: 127 adult patients were examined, belonging to the following groups: 1) DM+COVID (n=43 m/f 32/11); 2) COVID without DM (n=34, m/f 19/15); 3) without DM, without COVID (n=50, m/f 30/20). Patients with COVID-19 had moderate and severe disease. At the beginning of Covid-19 treatment and 6 months after recovery, general clinical, haematological and biochemical parameters were recorded, and the concentrations of serotonin, homocysteine, folic acid, and cardiovascular biomarker ST-2 in blood serum were assessed. The molecular genetic method of real-time polymerase chain reaction characterised polymorphisms of folate cycle genes: MTHFR 677 C>T and 1298 A>C, MTR 2756 A>G, and MTRR 66 A>G. Results. The distribution of patients by genotypes of folate cycle genes showed that group (1), compared to group (2), that group (1) compared to group (2) had a lower proportion of homozygous recessive mutations in the studied positions. Thus, in group 2, the recessive genotype MTRR 66 G/G was observed in 26 % of cases. A significant relationship was found between BMI and the initial serotonin serum level in the group (3) (R2=0,697), without a significant relationship between BMI and the initial values ​​of homocysteine, ST-2 and folic acid. As a result of regression analysis, significant differences were found in the list of factors that affect the change in serotonin and ST-2 serum levels in the two groups of patients during treatment; differences in the influence of pneumonia indicators and the MTRR 66 A>G gene were noted. Conclusions. The use of modern methods of molecular diagnostics, in particular the determination of folate cycle gene mutations, in combination with the assessment of the endothelium toxic product homocysteine ​​and the neurotransmitter serotonin serum levels, allowed us to obtain a mathematical justification for the features of changes in the studied indices that occurred in the post-COVID period in patients depending on the presence of type 2 diabetes